2018
DOI: 10.1080/14764172.2017.1400175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and efficacy of carbon dioxide therapy (carboxytherapy) versus mesolipolysis in the treatment of cellulite

Abstract: Carboxytherapy and mesolipolysis are safe and effective in cellulite treatment. Carboxytherapy is a promising alternative therapeutic modality for cellulite treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 17 publications
0
24
0
4
Order By: Relevance
“…The DCAGB course influenced patients' peripheral blood in all age groups like an antioxidant, significantly increasing erythrocyte peroxide resistance, which is largely associated with hypolypidemic carbon dioxide effect [15,14]. Subsequent to the DCAGB course exposure, most parameters reflecting the level of the LP processes showed significant oppression of the process, additionally elimination of the metabolic acidosis developed during the aging of the organism was observed, as well as increased alkaline reserve and improved peripheral blood oxygenation, which together contributed to the reduction of biological and cardiopulmonal age of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCAGB course influenced patients' peripheral blood in all age groups like an antioxidant, significantly increasing erythrocyte peroxide resistance, which is largely associated with hypolypidemic carbon dioxide effect [15,14]. Subsequent to the DCAGB course exposure, most parameters reflecting the level of the LP processes showed significant oppression of the process, additionally elimination of the metabolic acidosis developed during the aging of the organism was observed, as well as increased alkaline reserve and improved peripheral blood oxygenation, which together contributed to the reduction of biological and cardiopulmonal age of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Literature contains information on the role of CO2 in organism metabolism and functions regulation of its systems, on the presence of antioxidant properties of CO2; several mechanisms of its influence on the lipid peroxidation processes in animals and humans are presented etc. [12,13,14,15]. At the same time, the role of CO2 in the regulation of aging and biological age change is not sufficiently covered in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…14 Regarding wound healing resulting specifically from chronic venous insufficiency, it is known that the repair process occur slowly, and it is insufficient because the migration of cells is inefficient, which causes the chronicity of this condition as the region cannot be reepithelialised, 15 resulting in dysfunctional tissue in the affected area. 3 The literature on the improvement of this condition does not present concise and recent findings, so we consider the choice of the carboxytherapy in this study because the carbon dioxide used in this process is non-toxic, cost-effective, and safe 16,17 and I II III I II III I II III I II I II III I II III I II III I II respects the principle primum non nocerae (first of all not to prejudice), aiming to stimulate, or at least not inhibit, cell replication. 18 The present study confirmed the decrease of the inflammatory process after treatment with carboxytherapy, which promotes an increase of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect is achieved as a local treatment by a subcutaneous micro-injections administration of CO2 to multiple sites in the affected area (Brandi, 2010). This latter is also a subject to topical application in cosmetology for treatment of cellulite, stretch marks and in the rejuvenation of certain skin areas (Eldsouky et al, 2018). Specific and characteristic effects being observed during partial or full immersion of the human body in CO2-rich water or in dry-CO2 bath applications, which is similar to natural "mofetta gas-mix" effect that being used in some regions of Central Europe.…”
Section: Introductionmentioning
confidence: 95%